Building Collaborative Advantage in Hospital Systems: The Role of Supply Chain Collaboration, Innovation, and Digital Transformation in Class C Hospitals in Java Island - Syahdani Uli; Rina Anindita; Aprilita Rina Yanti Eff; Tantri Yanuar Rahmat Syah (International Journal of Engineering, Science and Information Technology, 2025)
This study aims to analyze the influence of transformational leadership, digital transformation, supply chain collaboration, and innovation on collaborative advantage and the performance of type C hospitals in Java, with government subsidies as a moderating variable. Using a quantitative approach and PLS-SEM analysis on 50 hospitals, the results show that most direct relationships between variables are insignificant, except for the influence of innovation on collaborative advantage and the influence of collaborative advantage on hospital performance, which are proven to be significant. In addition, government subsidies only play a significant role in strengthening the relationship between supply chain collaboration and collaborative advantage. These results confirm that collaborative advantage is a key factor in improving hospital performance, with innovation as its main driver. Meanwhile, transformational leadership and digital transformation have not shown a strong direct influence due to bureaucratic limitations and implementation readiness. These findings also indicate that government subsidies are more effective in the early stages of establishing collaborations, rather than directly improving performance. This study highlights the importance of external collaboration strategies and innovation in improving the competitiveness of public hospitals, as well as the importance of adapting global theories to the local context in developing health policies in Indonesia.